LOW SEX HORMONE BINDING GLOBULIN: A POTENTIAL PREDICTOR OF FUTURE GLUCOSE DYSREGULATION IN WOMEN - Heald, Adrian; Aamir; Laing, Ian; Anderson, Simon G; Livingston, Mark (Journal of Ayub Medical College Abbottabad, 2021)
We looked at the relation between baseline SHBG concentration and future glycaemic status over an up to 10 year period, for women who were normoglycaemic at baseline. In multiple linear regression analysis, a lower SHBG was associated with a higher fasting glucose independent of age and index of multiple deprivation (IMD). These findings suggest that a low SHBG level, at a relatively young age is a risk marker for future impaired glucose handling in women.